2013
DOI: 10.1002/ange.201300948
|View full text |Cite
|
Sign up to set email alerts
|

“Magic” Surface Clustering of Borazines Driven by Repulsive Intermolecular Forces

Abstract: It's a kind of magic: Hydroxy pentaaryl borazine molecules self‐assemble into small clusters (see structure) on Cu(111) surfaces, whereas with symmetric hexaaryl borazine molecules large islands are obtained. Simulations indicate that the observed “magic” cluster sizes result from long‐range repulsive Coulomb forces arising from the deprotonation of the BOH groups of the hydroxy pentaaryl borazine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 47 publications
1
11
0
Order By: Relevance
“…Whereas compound 1 features three phenyl (Ph) and three mesityl (Mes) groups bonded to the nitrogen and boron atoms, respectively, molecule 2 replaces the phenyl groups with peripherally protruding phenyl-4-ethynylphenyl moieties. Following the experimental protocols developed by us for borazine 1 , 56 , 57 molecule 2 was obtained after reaction of 4-ethynylphenylaniline with BCl 3 upon subsequent addition of three equivalents of MesLi following the route displayed in the Supporting Information.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas compound 1 features three phenyl (Ph) and three mesityl (Mes) groups bonded to the nitrogen and boron atoms, respectively, molecule 2 replaces the phenyl groups with peripherally protruding phenyl-4-ethynylphenyl moieties. Following the experimental protocols developed by us for borazine 1 , 56 , 57 molecule 2 was obtained after reaction of 4-ethynylphenylaniline with BCl 3 upon subsequent addition of three equivalents of MesLi following the route displayed in the Supporting Information.…”
Section: Resultsmentioning
confidence: 99%
“…Ruled by a delicate interplay of short-range van der Waals (vdW) attractions and long-range Coulomb repulsions between molecules, we have shown that a hydroxyl-pentaaryl borazine assembles in small clusters, which is in striking contrast with the large-island assembly obtained for molecule 1 (Scheme 1 ). 57 …”
Section: Introductionmentioning
confidence: 99%
“…Amongt he different functionalisation approaches, the replacement (i.e.,d oping) of one or more carbon atoms with electron-deficient or -rich heteroatoms is emerging as av ersatile strategyt ot une optoelectronic properties. [9] The insertion of third-group elements, such as borono ra luminium, introduces electronicv acancies (or holes), [10][11][12][13][14][15] whereas the insertion of fifth-and sixth-group elementse lectronicallye nriches carbonbased substrates to generate non-bonding states. [16][17][18][19] Phosphorescence is aforbidden radiativerelaxationo fanexcited state with spin symmetry different from that of the ground state.F or organic species, it mostly involves the decay from at riplet to as inglet state.…”
Section: Introductionmentioning
confidence: 99%
“…Clusters containing 10 molecules (decamers) are found to be much more stable compared to clusters containing 11 molecules (undecamers), see figure 22. For borazines on Cu(1 1 1), regular heptamers appear to be most stable [178]. In addition, clusters composed of 13 molecules appear in richer abundance compared to other clusters.…”
Section: Stability Of Few-molecule Islandsmentioning
confidence: 98%